Turbulent Events and Gas-Side Mass Transfer Coefficients in a Wavy Air-Water Stratified Flow - Mohsen Nasr Esfahany; Nazi Amanatchi (Iranian Journal of Chemistry & Chemical Engineering, 2011)
Turbulence structure on the gas side of a wavy stratified flow was experimentally investigated in a near horizontal 18.7 cm (H) 10 cm (W) 5.5m (L) rectangular duct.By applying the Variable Interval Time Averaging (VITA) technique to the hot wire anemometer measurements frequency of occurrence of turbulent events were detected near the air-water interface. Experimental results showed that frequency of occurrence of turbulent events over the waves increased with the interfacial shear at the interface. Mass transfer coefficients were calculated making use of eddy cell model and calculated turbulent event frequencies. Predicted mass transfer coefficients show good agreement with experimental correlation. Conditional averages of turbulent events were obtained by applying VITA technique to the measured instantaneous velocities. Despite near wall region, both ejection and sweep can initiate turbulent event at the interface.